THE INFLUENCE OF RELIGIOUS ATTITUDES ON VOCATIONAL HIGH SCHOOL STUDENTS'S WORK READINESS - Diyana Indah Sari; Suharno Suharno; Nugroho Agung Pambudi (Nozel : Jurnal Pendididikan Teknik Mesin, 2023)
This study aims to determine the influence of religious attitudes on vocational high school students's work readiness. This study used a quantitative approach with a descriptive design. The population in this study were all students of Vocational High School 1 Kismantoro, Vocational High School 1 Bulukerto, Vocational High School 1 Pracimantoro, a total of 2477 students, and the sample taken was 97 respondents. The sampling technique used in this research is simple random sampling technique formula is used to determine the number of samples Slovin. The method used in this research is a quantitative approach with a survey design. Data was collected by distributing closed questionnaires of 42 questions to respondents. The data analysis technique used in this research is simple linear regression analysis. The results showed that religious attitudes had a positive and significant effect on the work readiness of vocational high school students with an R square of 0.6451. This means that religious attitudes have an influence on the work readiness of vocational high school students by 64.51% and the rest is influenced by other variables.